2022
DOI: 10.4490/algae.2022.37.9.11
|View full text |Cite|
|
Sign up to set email alerts
|

Splitting blades: why genera need to be more carefully defined; the case for <italic>Pyropia</italic> (Bangiales, Rhodophyta)

Abstract: The trend in naming genera based almost exclusively on molecular data, and not on morphological diagnostic characters, is increasing. In bifurcating phylogenetic trees generic cut-offs are arbitrary, but at the bare minimum nomenclatural changes should be supported by multiple phylogenetic methodologies using appropriate models for all the various gene partitions, strong support with all branch support methods, and should also result in adding to our knowledge of the interrelationships of taxa. We believe that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“…The tree is drawn to scale, with branch lengths measured in the number of substitutions per site. Symbols: * , distinct sequences produced in this study; ** , species nomenclature according to Santiañez & Wynne 2020, Yang et al 2020 and Zuccarello et al 2022.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tree is drawn to scale, with branch lengths measured in the number of substitutions per site. Symbols: * , distinct sequences produced in this study; ** , species nomenclature according to Santiañez & Wynne 2020, Yang et al 2020 and Zuccarello et al 2022.…”
Section: Resultsmentioning
confidence: 99%
“…Brodie et al 1996Brodie et al , 1998, but also for other red algal species (e.g. Destombe & Doug-las 1991;Maggs et al 1992;Goff et al 1994;Zuccarello et al 1999) -in several isolates of both species in Europe. Herein, we provide an update of the nomenclature status for former P. hiemalis.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The global production of cultivated macroalgae more than doubles every decade, and the production of red algae has overtaken brown algae since 2010, dominating the market (Badis et al 2020b). Production of laver (Pyropia spp., formerly known as Porphyra) (Zuccarello et al 2022) has also doubled during the same period, primarily due to a rapid expansion in China and Korea, but this rapid development of aquaculture is followed by a similarly increasing economic burden of disease outbreaks (Cottier-Cook et al 2016, 2021. Disease management is a growing concern for Pyropia farmers, and now contributes up to half the running cost of a farm (Kim et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the bladed Bangiales is now divided into 14 genera, and molecular phylogenetic studies have revealed surprisingly high biodiversity in the bladed Bangiales. Recently, Zuccarello et al (2022) proposed that newly established genera should be restored to Pyropia because of the low confidence of branches in phylogenetic analyses. However, the scientific names in the present study follow Yang et al (2020).…”
Section: Introductionmentioning
confidence: 99%